EGO DEPLETION AND ITS EFFECT ON AUDITORS’ JUDGMENT AND DECISION-MAKING QUALITY - Mursita, Lufi Yuwana; Mustafida, Nurul; Rachmadia, Rizki (Jurnal Akuntansi dan Keuangan Indonesia, 2019)
This study aimed to examine the determinants of ego depletion and its effect on judgment and decision-making (JDM) quality. Auditing is one of the professions vulnerable to ego depletion, which is a temporary state of lack of cognitive resources to self-control caused by physical or psychological fatigue. Data were collected via online survey on 121 auditors in Indonesia who were selected by convenience sampling. The results showed that interpersonal conflict positively affected ego depletion. In line with ego depletion theory, the results supported previous research that ego depletion negatively affected JDM quality. Interestingly, this research also found that the level of industry-specific experience reduced the effect of ego depletion on JDM quality. In conclusion, psychological problems had a more significant influence on auditor cognitive resources than physical problems, which could then have an impact on his/her performance in generating judgments and decisions.